PRIMARY SCHOOL CURRICULUM DEVELOPMENT ORIENTATION IN THE PERSPECTIVE OF MILLER AND SELLER MODEL OF CURRICULUM - Agustinus Tanggu Daga (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research aims to describe Miller and Seller’s theoretical perspective on curriculum development in primary schools. A literature study method was applied to collect data from relevant sources. The study finds that Miller and Seller’s curriculum orientation involves three approaches: transmission, transaction, and transformation. In the transmission orientation, curriculum development emphasizes transferring knowledge, skills, and values to students through learning subjects. The learning process is teacher-centered, the strategy is expository, and evaluation relies on traditional tests. The transaction orientation emphasizes interaction between the curriculum and students, where the teacher acts as a facilitator to assist students in constructing knowledge. The learning strategy employs scientific approaches with active, collaborative, and inquiry-based methods, and evaluation uses authentic assessment. In the transformation orientation, the curriculum focuses on students’ personal and social transformation. The learning strategy encourages students to find the meaning and value of learning and to apply it in real life. Teachers act as motivators and facilitators, while evaluation emphasizes performance and behavior appraisal through authentic assessment. In conclusion, primary school curricula in the transmission orientation focus on academic subjects with an integrated organization. In the transaction orientation, the curriculum is designed to solve social problems using a scientific paradigm. In the transformation orientation, the curriculum aims to enable students to achieve personal and social transformation holistically.